A STUDY ON THE PSYCHOLOGICAL AND PHYSICAL EFFECTS OF ALCOHOL ADDICTION BETWEEN 2012-2017 AND 2018-2023 IN GOSTIVAR MUNICIPALITY - Vraynko, Adnan; Baki, Esra; Uslu, Beyhan; Zengin, Pınar (International Scientific Journal Vision, 2026)
Alcoholism is defined as a chronic condition of uncontrolled alcohol consumption that adversely affects an individual's physical, psychological, and social life. This condition is characterized by an inability to reduce or stop alcohol intake, an increase in tolerance, and the appearance of withdrawal symptoms when alcohol is absent. The development of alcoholism is significantly influenced by the interaction of genetic predisposition, environmental factors, psychological state, and socioeconomic conditions. Alcoholism not only leads to individual health problems but also contributes to the breakdown of family structures, a decrease in workforce productivity, and various societal issues. Its treatment is managed through multidisciplinary approaches including detoxification, pharmacological support, and psychotherapy. The aim of this article is to compare the prevalence and effects of alcoholism in Gostivar during the periods 2012-2017 and 2018-2023 The necessary data for the article was obtained from the examination logs at Neuropsychiatric Clinics in Gostivar.